Regulatory reforms of European network industries and the courts - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2010)
Regulatory reforms in European network industries are strongly influenced by legal decisions. The cases considered in this paper not only initiated the liberalization process of the markets for network services but also provided an important signaling function for the remaining regulatory problems: localization of network-specific market power, abolishment of grandfathering rights, ex ante regulation of network-specific market power instead of negotiated unregulated network access, incentive regulation instead of cost-based regulation. The process towards sector-symmetric market power regulation based on economically founded principles gains increasing relevance. Nevertheless, there are further reform potentials to be exhausted in the future.
Keywords: 330; Netzinfrastruktur; Regulierung; Reform; Netzzugang; Rechtsprechung; EU-Staaten